Construction of strawberry-like Ni3S2@Co9S8 heteronanoparticle-embedded biomass-derived 3D N-doped hierarchical porous carbon for ultrahigh energy density supercapacitors. Issue 29 (8th July 2019) - Wang, Shifu; Xiao, Zuoyi; Zhai, Shangru; Wang, Haisong; Cai, Weijie; Qin, Longfei; Huang, Jianying; Zhao, Di; Li, Zhongcheng; An, Qingda
Abstract : The design of advanced supercapacitors requires electrode materials that combine high surface area with a developed hierarchical porous structure to facilitate ion transport and electrolyte permeability. Abstract : The design of advanced supercapacitors requires electrode materials that combine high surface area with a developed hierarchical porous structure to facilitate ion transport and electrolyte permeability. Herein, we report a cross-linking and in situ sulfuration strategy for synthesizing nickel sulfide (Ni3 S2 ) nanocrystal-attached cobalt sulfide (Co9 S8 ) encapsulated on three-dimensional (3D) N-doped hierarchical porous carbon (Ni3 S2 @Co9 S8 /N-HPC). The Ni3 S2 @Co9 S8 /N-HPC composite was extensively studied using different characterization technologies. The results revealed that the obtained material integrated the advantages of a developed N-doped carbon framework (fast ion transport and excellent electrical conductivity) and transition metal sulfide species (high theoretical specific capacitance). Benefiting from the synergistic effect of a strawberry-like Ni3 S2 @Co9 S8 structure and 3D interconnected hierarchical porous carbon, the resulting Ni3 S2 @Co9 S8 /N-HPC composite exhibited an ultrahigh attractive specific capacitance of 1970.5 F g −1 at a current density of 0.5 A g −1 and excellent cycling stability with a capacitance retention of 89.5% after 5000 cycles at 10 A g −1 . In addition, an asymmetric supercapacitor (ASC) of Ni3 S2 @Co9 S8 /N-HPC//HPC was assembled in a 6 M KOH electrolyte. It delivered an energy density of 77.1 W h kg −1 at a power density of 263.3 W kg −1, and it remained as high as 36.1 W h kg −1 even at 25.9 kW kg −1 . It is believed that the presented work opens up a new strategy to fabricate high-performance supercapacitor electrodes.